Body mass index and body fat percentage in assessing obesity: An analytical study among the adolescents of Dibrugarh, Assam - Dimpymoni Saikia; Sultana Jesmin Ahmed; Hiranya Saikia; Ratna Sarma (Wolters Kluwer Medknow Publications, 2018)
Background: Body mass index (BMI) is one of the most commonly used indices to measure the weight status of an individual. However, it takes only height and weight of individual into account. The relative body composition can be calculated regardless of height and weight by body fat percentage (BF%). Objectives: The objectives of the study are (1) To assess the prevalence of obesity using BMI and BF% among early adolescents studying in schools of Dibrugarh. (2) To assess the relationship between BMI and BF%. Methods: A cross-sectional analytical study was conducted among 1200 school going adolescents of 10-14 years in Dibrugarh town for 1 year. Weight status was assessed using the World Health Organization-2007 reference for BMI and the McCarthy's body fat reference. Data were presented using percentages and mean with standard deviation. The correlation between the anthropometric variables was calculated using Pearson's correlation coefficient. Kappa statistics was used to analyze the agreement. Results: Total participants included in the analysis were 1096 with a response rate of 91.3%. The prevalence of overweight and obesity by BMI was 20.9% and 10.2%, respectively. According to BF%, overweight was present in 16.4% participants and 10.9% were obese. Of the 625 normal weight participants (according to their BMI), 9.0% were overweight and 1% were obese under BF% criteria. Again, of 682 participants who were normal by BF%, 15.2% were categorized as obese by BMI criteria. BMI and BF% had a significant high positive correlation (r = 0.70 and P < 0.001). The measurement of agreement by Kappa statistics was 0.621 which was significant (P < 0.001). Conclusions: BMI and BF% positively correlate with each other. BMI accompanied by BF% in the studies might give a better picture of the adiposity of an adolescent.